Memaksimalkan Peran Orang Tua Dalam Menumbuhkan Empati Pada Anak Di Keluarga Kristiani - Kosma Manurung (Institut Agama Kristen Negeri Kupang, 2022)
Empathy is the root of morality and should be taught to children. The best place to teach empathy is in the family. Parents are in the very right position to teach empathy to their children. This research article intends to maximize the role of parents in growing children's empathy in Christian families. By using the method of description and literature review to support the description of Bible stories related to empathy, the importance of empathy for children, and the role that parents can play in fostering empathy in children. It is concluded that parents are able to play a maximum role in fostering children's empathy when they understand that parents are the main system in educating children, being proactive, having sensitivity, and positioning themselves to act as coaches for children's empathy.